Pengaruh Harapan Orang Tua dan Self-Efficacy Akademik terhadap Kecenderungan Fear of Failure pada Siswa: Analisis Perbandingan antara Siswa Kelas Unggulan dan Siswa Kelas Reguler - Abdul Muhid; Alfiatul Mukarromah (IAI Darussalam, 2018)
This study aims to examine the influence of parent expectation and academic self-efficacy on student’s fear of failure tendencies. In addition, this study also aims to examine the average comparison of parent expectation, academic self-efficacy, and student’s fear of failure tendencies between students of excellent class program and students of reguler class program. This study uses a quantitative approach with survey methods. The subjects of this study amounted to 271 students, 134 students of excellent class program and 137 students of reguler class program. The results showed that there was a significant influence of parent expectation and academic self-efficacy on student’s fear of failure tendencies, howeverthe results showed no significant differences the average comparison of parent expectation, academic self-efficacy, and student’s fear of failure tendencies between students of excellent class program and students of reguler class program